Characteristics and Factors for Short-Term Functional Outcome in Stroke Patients With Atrial Fibrillation, Nationwide Retrospective Cohort Study - Song, Tae-Jin; Baek, In-Young; Woo, Ho Geol; Kim, Yong-Jae; Chang, Younkyung; Kim, Bum Joon; Heo, Sung Hyuk; Jung, Jin-Man; Oh, Kyungmi; Kim, Chi Kyung; Yu, Sungwook; Park, Kwang Yeol; et al. (Frontiers in Neurology, 2019)
Background and aims: Atrial fibrillation (AF) is a major cause of ischaemic stroke; however, detailed clinical data and prognostic factors for stroke patients with AF are lacking in Korea. We aimed to investigate clinical information and factors associated with functional outcomes of stroke patients with AF from the Korean nationwide ATrial fibrillaTion EvaluatioN regisTry in Ischemic strOke patieNts (K-ATTENTION) database. Methods: From January 2013 to December 2015, consecutive clinical information from acute stroke patients with AF or history of AF was collected from 11 centers in Korea. Collected data included demographics, risk factors, pre-stroke medication, stroke severity, stroke subtypes, concomitant cerebral atherosclerosis, brain image findings, recanalization therapy, discharge medication and functional outcome at three months after index stroke. Results: A total of 3,213 stroke patients (mean age, 73.6±9.8 years; female, 48.6%) were included. The mean CHA2DS2-VASc score was 4.9. Among the 1,849 (57.5%) patients who had brain image and functional outcome data, poor outcome (modified Rankin scale >2) was noted in 53.1% (981/1,849) of patients. After adjusting for age, sex, and variables that had a p <0.05 in univariate analysis or well-known factors for functional outcome, presence of asymptomatic extracranial cerebral atherosclerosis (odd ratio (OR) 1.96, 95% confidence interval (CI) 1.36–2.82, p=0.001) and less frequent prior stroke statin intake (OR 0.69, 95% CI 0.49–0.98, p=0.038) were associated with poor functional outcome. Conclusion: Our results suggest that presence of non-relevant extracranial cerebral atherosclerosis may affect poor functional outcome and prior stroke statin therapy may be feasible in Korean stroke patients with AF.